Barang Bekas Menjadi Idola: Analisis Faktor Pengaruh Perceived Value pada Perilaku Thrifting - Ayudia Popy Sesilia; Findy Suri N (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
This study aims to identify the factors that affect Perceived Value (PV) among thrifting behavior. PV is understood as the consumer’s perception of product benefits compared to the sacrifices made, including price, time, and potential risk. The population in this study comprised all consumers who made purchases within the last six months, totaling 1,426 transactions. From this population, 201 respondents were selected using an accidental sampling technique. The analysis method used in this study is exploratory factor analysis with Principal Component Analysis extraction method. The findings revealed six main factors that affect PV based on extraction value, namely personal value (0.701), service value (0.655), shopping experience (0.627), image value (0.619), price (0.571), and perceived risk (0.520). Results indicate that consumers’ PV is more strongly shaped by psychological aspects, shopping experiences, and service quality rather than the physical attributes of products. These findings strengthen the understanding that consumer behavior in thrift stores is not only driven by price, but also by social identity, emotional satisfaction, and positive store image, which can serve as a basis for more targeted marketing strategies.